CITED4 gene therapy protects against maladaptive cardiac remodeling after ischemia/reperfusion injury in mice - Lerchenmüller, Carolin; Hastings, Margaret H.; Rabolli, Charles P.; Betge, Fynn; Roshan, Mani; Liu, Laura X.; Liu, Xiaojun; Heß, Chiara; Roh, Jason D.; Platt, Colin; Bezzerides, Vassilios; Busch, Martin; et al. (Molecular therapy, 2024)
Cardiac signaling pathways functionally important in the heart’s response to exercise often protect the heart against pathological stress, potentially providing novel therapeutic targets. However, it is important to determine which of these pathways can be feasibly targeted in vivo. Transgenic overexpression of exercise-induced CITED4 has been shown to protect against adverse remodeling after ischemia/reperfusion injury (IRI). Here we investigated whether somatic gene transfer of CITED4 in a clinically relevant time frame could promote recovery after IRI. Cardiac CITED4 gene delivery via intravenous AAV9 injections in wild type mice led to an approximately 3-fold increase in cardiac CITED4 expression. After 4 weeks, CITED4-treated animals developed physiological cardiac hypertrophy without adverse remodeling. In IRI, delivery of AAV9-CITED4 after reperfusion resulted in a 6-fold increase in CITED4 expression 1 week after surgery, as well as decreased apoptosis, fibrosis, and inflammatory markers, culminating in a smaller scar and improved cardiac function 8 weeks after IRI, compared with control mice receiving AAV9-GFP. Somatic gene transfer of CITED4 induced a phenotype suggestive of physiological cardiac growth and mitigated adverse remodeling after ischemic injury. These studies support the feasibility of CITED4 gene therapy delivered in a clinically relevant time frame to mitigate adverse ventricular remodeling after ischemic injury.